Answer:
[tex]cos(\theta)=-\frac{\sqrt{35} }{6}[/tex]
Step-by-step explanation:
Recall the negative angle identity for the sine function:
[tex]sin(- \theta)=-sin(\theta)[/tex]
Then, we can find the value of [tex]sin(\theta)[/tex]:
[tex]sin(\theta)=-sin(-\theta)\\sin(\theta) =-(-\frac{1}{6} )\\sin(\theta)= \frac{1}{6}[/tex]
Now recall the definition of the tangent function:
[tex]tan(\theta)=\frac{sin(\theta)}{cos(\theta)}[/tex]
Therefore, now that we know the value of [tex]sin(\theta)[/tex], we can solve in this equation for [tex]cos(\theta)[/tex]
[tex]tan(\theta)=\frac{sin(\theta)}{cos(\theta)}\\-\frac{\sqrt{35} }{35} =\frac{1/6}{cos(\theta)} \\cos(\theta)=-\frac{\frac{1}{6} }{\frac{\sqrt{35} }{35} } \\cos(\theta)=-\frac{35}{6\,\sqrt{35} } \\cos(\theta)=-\frac{\sqrt{35} }{6}[/tex]